2015
DOI: 10.1111/jeu.12203
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cytosolic Heat Shock Protein 70 Ssa5 in the Ciliate Protozoan Tetrahymena thermophila

Abstract: Heat shock protein 70 (Hsp70) is a member of a family of conserved chaperone proteins whose function is well investigated in many model organisms. Here we focus on an Hsp70 called Ssa5 in the ciliate protozoan Tetrahymena thermophila, and reveal that its translation is heat inducible as for general Hsps. Moreover, the protein is abundantly expressed in the cytoplasm during sexual reproduction (conjugation) as well as in response to heat-stress. Knocking out of SSA5 (ΔSSA5) does not affect the survival of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…For one, HSP with reproductive functions (HSP R ) might help activate HSP with stress-related functions (HSP S ) upon exposure to environmental stress, benefitting either the individuals that undergo sexual reproduction, or their resulting offspring, or both. This hypothesis is consistent with observations in the ciliate Tetrahymena thermophila, where the cytosolic HSP70 SSA5 chaperone has a crucial role in pronuclear fusion during fertilization and is also expressed in response to heat stress-without directly contributing to cell survival however [43,44]. In a non-mutually exclusive fashion, the expression of HSP R might also enhance survival by reducing sensitivity to environmental alterations.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…For one, HSP with reproductive functions (HSP R ) might help activate HSP with stress-related functions (HSP S ) upon exposure to environmental stress, benefitting either the individuals that undergo sexual reproduction, or their resulting offspring, or both. This hypothesis is consistent with observations in the ciliate Tetrahymena thermophila, where the cytosolic HSP70 SSA5 chaperone has a crucial role in pronuclear fusion during fertilization and is also expressed in response to heat stress-without directly contributing to cell survival however [43,44]. In a non-mutually exclusive fashion, the expression of HSP R might also enhance survival by reducing sensitivity to environmental alterations.…”
Section: Introductionsupporting
confidence: 91%
“…Among these genes, Hsp70Pt04 has alongside Hsp70Pt01 and Hsp70Pt03 the highest level of sequence similarity to the ciliate Tetrahymena thermophila's HSP70 SSA5 (Figure S3). SSA5 is a key protein for pronuclear fusion during fertilization and is also expressed during development and in response to heat-stress [43]. Similarly, SSA5 homologs in P. tetraurelia are expressed throughout development ( Figure S3) and are inducible after heat shock exposure (Hsp70Pt03 and Hsp70Pt04; [73]) or up-regulated after a 3week long period of starvation (Hsp70Pt01; [74]).…”
Section: Transcriptional Changes During Sexual Development Are Couplementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when BER is compromised, γH2AX foci are formed, suggesting that DSBs are induced, which are repaired after G 1 (Wossidlo et al, 2010; Ladstätter and Tachibana-Konwalski, 2016). Thus, while mammals require karyogamy to induce the epigenetic modifications necessary for embryonic developmental programming (Zhou and Dean, 2015), Tetrahymena gametic nuclei can differentiate into MACs and MICs without karyogamy (Fukuda et al, 2015). Therefore, chromatin remodeling in Tetrahymena pronuclei might resemble zygote reprogramming rather than mammalian male pronuclear chromatin remodeling, in that the differentiated germline pronucleus is re-set to a dedifferentiated progenitor of new somatic and germline nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that in the ciliate Tetrahymena thermophila the heat shock protein Ssa5 is abundantly expressed in response to heat stress as well as during sexual reproduction. A specific involvement of a heat shock protein in pronuclei fusion during conjugation was suggested (Fukuda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%